Pain interference and alcohol, nicotine, and cannabis use disorder in a national sample of substance users. (1st May 2018) - McDermott, Katherine A.; Joyner, Keanan J.; Hakes, Jahn K.; Okey, Sarah A.; Cougle, Jesse R.
Highlights: Pain interference was examined as a predictor of dependence in substance users. Pain interference predicted increased alcohol and nicotine dependence. Pain interference was associated with cannabis use disorder for women but not men. High pain interference predicted nicotine dependence development in men only. Abstract: Background: Pain interference is associated with substance use, but has yet to be considered as a potential indicator of SUDs among substance users. We sought to examine whether moderate and high pain interference would confer risk for SUDs in ever and weekly users. Methods: Using data from the National Epidemiologic Survey on Alcohol and Related Conditions, logistic regression analyses were conducted to examine the association between pain interference and concurrent and prospective alcohol and nicotine dependence, as well as concurrent cannabis use disorder. Those with no/low pain were used as the reference group. Gender was examined as a moderator. Results: Controlling for relevant covariates, moderate pain interference was associated with past year alcohol (odds ratio [OR] = 1.33, 95% CI, 1.16–1.52, p <  .001) and nicotine (OR = 1.41, 95% CI 1.27–1.56, p <  .001) dependence among ever users. In prospective analyses, moderate pain interference predicted the development of alcohol (Moderate: OR = 1.56, 95% CI, 1.39–1.75, p <  .001) and nicotine (OR = 1.37, 95% CI, 1.14–1.65, p <  .001) dependence. Similar results were found with high pain and for weekly users. Both moderate and high pain interference were associated with past-year occurrence of cannabis use disorder for women but not men. High pain predicted the development of nicotine dependence exclusively among males. Conclusion: Pain interference may confer risk for the occurrence of cannabis use disorder among female cannabis users and the occurrence and development of alcohol and nicotine dependence among users of both genders. Pain interference may be an important factor to monitor in these populations.